2012
DOI: 10.1111/jzo.12005
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in threespine stickleback lateral plates

Abstract: The study of asymmetry can provide insights into genetic and environmental influences on organismal development. Directional asymmetry (DA) can be either adaptive or non‐adaptive, whereas fluctuating asymmetry (FA) – defined as small non‐directional departures from symmetry in bilateral traits – is thought to be an indicator of genetic or environmental stress experienced during development. Using data from 28 European populations, we assessed the degree of DA and FA in the lateral plates of threespine stickleb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…(4) Plate position asymmetry differed between structural and nonstructural plates. In contrast to observations made in freshwater populations (Bergstrom and Reimchen 2000;Loehr et al 2013), only a single individual exhibited structural asymmetry among all marine individuals. (5) Finally, asymmetry did not vary significantly with standardized genome-wide heterozygosity, but was clearly associated with Eda genotype, even in genotype-phenotype mismatched individuals.…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…(4) Plate position asymmetry differed between structural and nonstructural plates. In contrast to observations made in freshwater populations (Bergstrom and Reimchen 2000;Loehr et al 2013), only a single individual exhibited structural asymmetry among all marine individuals. (5) Finally, asymmetry did not vary significantly with standardized genome-wide heterozygosity, but was clearly associated with Eda genotype, even in genotype-phenotype mismatched individuals.…”
Section: Discussioncontrasting
confidence: 74%
“…That is an occurrence of 0.35%, as opposed to freshwater reports varying from 1.1% to 4.8% (Bergstrom and Reimchen ; Loehr et al. ). This contrast suggests that canalization of structural plates may be under relaxed selection in the freshwater environment (Trokovic et al.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Directional asymmetry is not a rare effect in Diptera Pélabon and Hansen, 2008;Soto et al, 2010), as well in other invertebrate (Graham et al, 1998;Schneider et al, 2003) and vertebrate groups (Kark, 2001;Marchand et al, 2003;Loehr et al, 2013). In Diptera, suggested that the genetic basis of DA has been conserved over evolutionary time due to the existence of a left-right axis determining the position of imaginal disks (developmental precursors of wings) on each side of the body.…”
Section: Discussionmentioning
confidence: 96%